Estimating Death Injuries Due to Road Traffic Accidents in Karachi Pakistan - Imran, Shahla; Memon, Haya Afzal; Ahmad, Zakiuddin (Indus Journal of Bioscience Research, 2025)
Background: Road traffic accidents (RTAs) remain a leading cause of injury and death worldwide. In Karachi, Pakistan, the prevalence of road traffic-related fatalities and injuries has significantly increased, raising concerns about the role of toxicological factors, such as alcohol and drug use, in these incidents. Objectives: The primary objective of this study was to estimate the death and injury rates due to road traffic accidents in Karachi, Pakistan. Study Design & Setting: This was a cross-sectional study conducted in Karachi, Pakistan, in the city 19 December 2024 to 19 June 2025. Methodology: Using data from 150 road traffic accident victims admitted to major hospitals in Karachi, a structured data collection form was employed to extract information from medical records. Demographic characteristics, types of injuries, and toxicological findings (including alcohol and drug use) were recorded. The data were analyzed using descriptive statistics, and p-values were calculated to determine the significance of the association between toxicological factors and injury severity. Results: The study found that 30% of victims tested positive for alcohol, and 13.3% had used drugs. Alcohol use was significantly correlated with fatal injuries, while drug use was more commonly associated with non-fatal injuries. Male victims were more likely to be intoxicated and sustain fatal injuries compared to females. Conclusion: Toxicological factors, especially alcohol use, play a significant role in road traffic accident fatalities in Karachi. This highlights the need for stricter enforcement of traffic laws and public awareness campaigns to reduce intoxicated driving.